2016
DOI: 10.13189/ujer.2016.040717
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Dimensions of Perfectionism on Anxiety Sensitivity

Abstract: This study investigated the relationship between dimensions of perfectionism and anxiety sensitivity. The study group is composed by 398 (211 female; 187 male) students who were studying at the pedagogical formation certificate program at Mugla Sitki Kocman University. The data were collected by using the Frost Multidimensional Perfectionism Scale and Anxiety Sensitivity Index-R. Pearson product-moment correlation analysis was employed to study the relationships between anxiety sensitivity and dimensions of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
(67 reference statements)
1
2
0
1
Order By: Relevance
“…Additionally, and consistent with themes found throughout this project, the authors noted the marked anxiety in those individuals with the highest scores in socially-prescribed perfectionism (Akram et al, 2015). Erozkan (2016) identified six key areas that are complicit in a positive association with anxiety and perfectionism: doubts about actions, high personal standards, high parental expectations, and a tendency to perceive one's parents as being critical. Damian et al (2017) also found that individuals who displayed perfectionist strivings coupled with marked perfectionistic concerns were a risk factor for maladaptive ruminative thinking and inherently present in those who display perfectionistic personality traits.…”
Section: Psychological Consequences Of Perfectionismsupporting
confidence: 70%
“…Additionally, and consistent with themes found throughout this project, the authors noted the marked anxiety in those individuals with the highest scores in socially-prescribed perfectionism (Akram et al, 2015). Erozkan (2016) identified six key areas that are complicit in a positive association with anxiety and perfectionism: doubts about actions, high personal standards, high parental expectations, and a tendency to perceive one's parents as being critical. Damian et al (2017) also found that individuals who displayed perfectionist strivings coupled with marked perfectionistic concerns were a risk factor for maladaptive ruminative thinking and inherently present in those who display perfectionistic personality traits.…”
Section: Psychological Consequences Of Perfectionismsupporting
confidence: 70%
“…A. Erozkan [7] пояснює складність як структури перфекціонізму, так, вочевидь, і його визначення / розуміння, тим, що у ньому, як у комплексі, інтегральній конструкції, поєднані когнітивний, емоційний, мотиваційний і поведінковий фактори / процеси. Він зазначає, що, хоча остаточне і прийняте всіма науковцями, які вивчають проблему перфекціонізму, визначення цього явища наразі відсутнє, проте існує принципова згода щодо його повторюваних вченими характеристик: встановлення людиною найвищих / нереальних стандартів своєї діяльності та її переживання щодо власної відповідності / невідповідності їм.…”
Section: секція XXVIII психологія та психіатріяunclassified
“…The evidence seems to show that elevated levels of pathological perfectionism may underlie a variety of co-morbid anxiety psychopathology. It is remarkable that the attributes that pertain to SOPS/PCP include all of the above characteristics ascribed to mal-adaptive perfectionism, self-handicapping and anxiety sensitivity (Erozkan, 2016;Levinson et al, 2015;Gnilka et al, 2012;Egan et al, 2011;Kearns et al, 2008;Schweitzer & Hamilton, 2002;Frost et al, 1990).…”
Section: Mutual Benefits Of Sops/pcp's Theory and Other Researchmentioning
confidence: 99%